PROTECTION FROM COSMIC RADIATION IN LONG-TERM MANNED SPACEFLIGHTS - Marco Durante (Annales Kinesiologiae, 2015)
Current space programs are shifting toward planetary exploration, and in particular towards human missions to the moon and Mars. Space radiation, comprised of energetic protons and heavy nuclei, has been shown to produce distinct biological damage compared to radiation on Earth, leading to large uncertainties in the projection of health risks. Even if uncertainties in risk assessment will be reduced in the next few years, there is little doubt that appropriate countermeasures have to be taken to reduce the exposure or the biological damage produced by cosmic radiation. In addition, it is necessary to provide effective countermeasures against solar particle events, which can produce acute effects, even life threatening, for inadequately protected crews. Unfortunately, passive (bulk) shielding is currently unable to provide adequate protection, because cosmic rays have very high energy and nuclear fragmentation in the absorbers produce light fragments. Material science could provide new materials with better shielding properties for space radiation. Active (magnetic) shielding could be an interesting alternative, pending technical improvements.